2022
DOI: 10.3389/ffunb.2022.957021
|View full text |Cite
|
Sign up to set email alerts
|

The emerging threat antifungal-resistant Candida tropicalis in humans, animals, and environment

Abstract: Antifungal resistance in humans, animals, and the environment is an emerging problem. Among the different fungal species that can develop resistance, Candida tropicalis is ubiquitous and causes infections in animals and humans. In Asia and some Latin American countries, C. tropicalis is among the most common species related to candidemia, and mortality rates are usually above 40%. Fluconazole resistance is especially reported in Asian countries and clonal spread in humans and the environment has been investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 145 publications
0
12
0
Order By: Relevance
“…Similarly, antifungal resistance to FCZ has been reported in Candida species from tropical freshwater environments in Brazil and China [ 9 , 53 , 54 , 55 ]. The presence of environmental yeasts with high resistance to FCZ is probably due to the fact that this azole is the most widely used antifungal in humans and animals, and it is among the most reported drugs in hospital and home wastewater [ 56 , 57 ]. In addition, there are fungicides routinely used in agriculture that share the action mechanism of azoles, which can generate cross-resistance in yeasts found in these aquatic environments [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, antifungal resistance to FCZ has been reported in Candida species from tropical freshwater environments in Brazil and China [ 9 , 53 , 54 , 55 ]. The presence of environmental yeasts with high resistance to FCZ is probably due to the fact that this azole is the most widely used antifungal in humans and animals, and it is among the most reported drugs in hospital and home wastewater [ 56 , 57 ]. In addition, there are fungicides routinely used in agriculture that share the action mechanism of azoles, which can generate cross-resistance in yeasts found in these aquatic environments [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of environmental yeasts with high resistance to FCZ is probably due to the fact that this azole is the most widely used antifungal in humans and animals, and it is among the most reported drugs in hospital and home wastewater [ 56 , 57 ]. In addition, there are fungicides routinely used in agriculture that share the action mechanism of azoles, which can generate cross-resistance in yeasts found in these aquatic environments [ 56 , 57 , 58 ]. In Asia, some studies reported a significant increase in resistant C. tropicalis isolated from poultry, and this has been associated with the extensive use of azoles in agriculture [ 56 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, Aspergillus and Candida species were used as test organisms because the resistance of Aspergillus and Candida species to commercially available drugs have been increasingly reported due to susceptibility test standards and with increasing use of antifungal agents (Arendrup 2014). Candida tropicalis is predominant and causes infections in animals and humans (Lima et al 2022). Candidiasis is a broad term that refers to mucosal, cutaneous, and deep-rooted organ infections caused by fungi of the Candida genus.…”
mentioning
confidence: 99%
“…In Asia and some parts of Latin America, C. tropicalis is among the most common species related to candidemia, and mortality rates are usually 40%. A recent study suggests an increasing ubiquity of fluconazole and multidrug resistance of C. tropicalis retrieved from humans (Lima et al 2022). On the other hand, aspergillosis is a severe clinical problem that is caused by Aspergillus species, especially in immunocompromised patients, thus Aspergilli has become an opportunistic fungal pathogen (Shishodia et al 2019).…”
mentioning
confidence: 99%